Polyacenaphthene curing agent, resin composition, and multilayer insulating film
By combining polyacene-based curing agents with a specific structure with thermosetting resin, the dielectric and mechanical properties of the resin composition are optimized, and the challenges of existing low-loss materials in improving mechanical strength and processing properties are solved, achieving excellent dielectric and processing properties.
Patent Information
- Application Number
- CN202411899067.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Existing low-loss materials have challenges in improving mechanical strength and machining performance, and it is difficult to further improve their performance while maintaining low-loss characteristics.
The polyacene-based curing agent with a specific structure is combined with a thermosetting resin to optimize the dielectric and mechanical properties of the resin composition through the curing reaction, and the processing performance of the resin composition is improved by the introduction of acene-based group.
The low loss characteristics, excellent dielectric properties, enhanced mechanical properties and improved processing properties of the resin composition are achieved, solving the shortcomings of existing materials in these aspects.
Smart Images

Figure BDA0005202652800000022 
Figure BDA0005202652800000042 
Figure BDA0005202652800000061
Abstract
Description
Technical Field
[0001] The present invention relates to the field of technology, in particular to a polyacenaphthylene curing agent, a resin composition and a laminated insulating film. Background Art
[0002] In the field of high-speed signal transmission, signal integrity is a key factor that cannot be ignored in packaging design. Signal loss is mainly divided into two parts: conduction loss and radiation loss. Dielectric constant and loss tangent are two core parameters that affect loss. A high dielectric constant will slow down the transmission speed of the signal, while a high loss tangent will increase the loss of signal energy, thus affecting the transmission quality of the signal and the overall performance of the electronic equipment.
[0003] In order to meet these challenges, the selection of low-loss materials has become the primary task in the preparation of Low Loss laminated insulation films. Ideal low-loss materials should have the characteristics of low dielectric constant and low loss tangent, while also ensuring excellent mechanical properties and processability. At present, PTFE, LCP, PI and their modified materials are widely used in the preparation of such films due to their low-loss characteristics. The difficulty in preparing Low Loss laminated insulation films lies in how to further improve their mechanical strength and processing performance while maintaining the low-loss characteristics of the material. Therefore, it is necessary to propose a new solution to solve the above problems. Summary of the invention
[0004] In view of this, the present invention aims to address the deficiencies in the prior art, and its main purpose is to provide a polyacenaphthylene curing agent, a resin composition and a laminated insulating film, which have low loss characteristics as well as excellent mechanical properties and processing properties.
[0005] To achieve the above purpose, the present invention adopts the following technical solutions:
[0006] A polyacenaphthylene curing agent, the structural formula of the polyacenaphthylene curing agent is as follows:
[0007] R is a hydrocarbon chain segment, and n and m are both integers greater than 1.
[0008] As a preferred embodiment, both n and m are integers of 1-15, wherein n is preferably an integer of 3-12, more preferably an integer of 5-12, and m is preferably an integer of 3-10.
[0009] As a preferred solution, the number average molecular weight of the polyacenaphthylene curing agent is 300-5000, and preferably 1000-2800.
[0010] As a preferred embodiment, the structural formula of the polyacenaphthylene curing agent is
[0011]
[0012] Any one of .
[0013] A resin composition comprising the following components in parts by weight:
[0014] 80-120 parts of thermosetting resin, 0.01-10 parts of curing accelerator, 300-500 parts of inorganic filler and 80-180 parts of the aforementioned polyacenaphthylene curing agent.
[0015] As a preferred solution, the thermosetting resin is at least one of polyimide resin, phenoxy resin, polyamide resin, polyamideimide resin and polyvinyl acetal resin, preferably one of polyimide resin and phenoxy resin or a mixture of both.
[0016] As a preferred solution, the number average molecular weight of the thermosetting resin is 2000-100000, and preferably 5000-50000.
[0017] As a preferred embodiment, the curing accelerator is one of an imidazole curing accelerator, a tertiary amine curing accelerator, a phosphine curing accelerator, a photobase generator, and a sulfonium salt curing accelerator; the inorganic filler is at least one of silica, alumina, barium sulfate, talc, clay, mica, magnesium oxide, aluminum hydroxide, aluminum nitride, boron nitride, silicon nitride, glass powder, glass frit, glass fiber, and carbon fiber. The inorganic filler is preferably silica, and more preferably fused silica.
[0018] As a preferred solution, the equivalent ratio of the thermosetting resin to the polyacenaphthylene curing agent is 1:(0.3-2), preferably 1:(0.6-1.5).
[0019] A laminated insulating film is prepared by the following steps: using a coating machine to coat the aforementioned resin composition on a base film, wherein the base film is made of PET or BOPP material; after coating, drying is performed, the drying temperature is 100°C, and the drying time is 10 minutes; after drying, the base film is removed to obtain a laminated insulating film.
[0020] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:
[0021] By selecting a polyacenaphthylene curing agent with a specific structure, in which R is a hydrocarbon chain segment, after R is replaced in the curing reaction with a thermosetting resin, a resin composition with excellent dielectric properties can be obtained. In addition, by introducing acenaphthylene groups into the resin composition, the mechanical properties of the resin composition are enhanced, the thermal expansion coefficient is reduced, and thus the processing performance of the resin composition is improved.
[0022] In order to more clearly illustrate the structural features and effects of the present invention, the present invention is described in detail below in conjunction with specific embodiments: DETAILED DESCRIPTION
[0023] The present invention discloses a polyacenaphthylene curing agent, the structural formula of the polyacenaphthylene curing agent is as follows:
[0024] R is a hydrocarbon chain segment, and n and m are both integers greater than 1; specifically, as a preferred embodiment, n and m are both integers of 1-15, wherein n is preferably an integer of 3-12, more preferably an integer of 5-12, and m is preferably an integer of 3-10; and the number average molecular weight of the polyacenaphthylene curing agent is 300-5000, and the number average molecular weight is preferably 1000-2800; the structural formula of the polyacenaphthylene curing agent is
[0025]
[0026] Any one of .
[0027] The present invention also discloses a resin composition, comprising the following components in parts by weight:
[0028] 80-120 parts of a thermosetting resin, 0.01-10 parts of a curing accelerator, 300-500 parts of an inorganic filler, and 80-180 parts of the aforementioned polyacenaphthylene curing agent; within a specific weight range of the thermosetting resin, the flow characteristics of the obtained resin composition, the bending resistance after curing, and the heat resistance become more excellent, the thermosetting resin is at least one of a polyimide resin, a phenoxy resin, a polyamide resin, a polyamideimide resin, and a polyvinyl acetal resin, preferably one of a polyimide resin and a phenoxy resin or a mixture of the two; the number average molecular weight of the thermosetting resin is 2000-100000. , and its number average molecular weight is preferably 5000-50000; the curing accelerator is one of imidazole curing accelerator, tertiary amine curing accelerator, phosphine curing accelerator, photobase generator, and sulfonium salt curing accelerator; the inorganic filler is at least one of silica, alumina, barium sulfate, talc, clay, mica, magnesium oxide, aluminum hydroxide, aluminum nitride, boron nitride, silicon nitride, glass powder, glass frit, glass fiber, and carbon fiber, and the inorganic filler is preferably silica, and more preferably molten silica; the equivalent ratio of the thermosetting resin to the polyacenaphthylene curing agent is 1: (0.3-2), preferably 1: (0.6-1.5).
[0029] The present invention also discloses a laminated insulating film, which is prepared by the following steps: using a coating machine to coat the aforementioned resin composition on a base film, wherein the base film is made of PET or BOPP material; after coating, drying is performed, the drying temperature is 100°C, and the drying time is 10 minutes; after drying, the base film is removed to obtain a laminated insulating film.
[0030] The following is explained through multiple examples and comparative examples, and the raw materials and proportions used are shown in Table 1 and Table 2 respectively.
[0031] Material Manufacturer Code Acenaphthylene Maclean A787703 Polyacenaphthylene curing agent A self made Polyacenaphthylene curing agent B self made Polyacenaphthylene curing agent C self made Polyimide resin Yamato Chemical Industry Co., Ltd. BMI-100 Phenoxy resin Saudi Basic Industries SA9000 Cyanate A CarbonResin CE 220 Cyanate B Primaset PT-30 Curing accelerator Shikoku Kasei 2E4M Inorganic fillers Admatechs Co., Ltd. SC2050-KC
[0032] Table 1
[0033] The preparation method of polyacenaphthylene curing agent A is as follows:
[0034] Take 400g of acenaphthylene, 400mL of xylene and an appropriate amount of divinylbenzene, put these three substances together into a reactor equipped with a stirrer, a condenser, a thermometer and a 1000mL nitrogen protection device, stir, heat, slowly raise the temperature of the reaction system to 90°C, and continue stirring for a period of time until the above three substances are completely dissolved, and the solution reaches a uniform state; then, accurately weigh 3.2g of benzoyl peroxide BPO, add it to the reaction system, and stir for 4 hours. During the 4-hour reaction process, the stirrer should continue to stir, the nitrogen protection device should continue to provide nitrogen protection, and the condenser should continue to condense and reflux to ensure the stability of the reaction system. After 4 hours of reaction, the polymerization reaction is completed, and finally a polymerization liquid A is obtained; through 1H-NMR, GPC and FT-IR analysis, it is confirmed that the polymerization liquid A contains the compound represented by the following structural formula,
[0035]
[0036] The polyacenaphthylene curing agent A has a number average molecular weight of 1,400.
[0037] The preparation method of polyacenaphthylene curing agent B is as follows:
[0038] Take 400g of acenaphthylene, 400mL of xylene and an appropriate amount of 1,2-bis(p-vinylphenyl)methane, put these three substances into a 1000mL reactor equipped with a stirrer, a condenser, a thermometer and a nitrogen protection device, stir, heat, and slowly raise the temperature of the reaction system to 90°C. Continue stirring for a period of time until the above three substances are completely dissolved, and the solution reaches a uniform state; then, accurately weigh 3.2g of benzoyl peroxide BPO, add it to the reaction system, and stir for 4 hours. During the 4-hour reaction process, the stirrer must continue to stir, the nitrogen protection device must continue to provide nitrogen protection, and the condenser must continue to condense and reflux to ensure the stability of the reaction system. After 4 hours of reaction, the polymerization reaction is completed, and finally a polymerization liquid B is obtained. Through 1H-NMR, GPC and FT-IR analysis, it is confirmed that the polymerization liquid B contains the compound represented by the following structural formula,
[0039]
[0040] The polyacenaphthylene curing agent B has a number average molecular weight of 1,700.
[0041] The preparation method of polyacenaphthylene curing agent C is as follows:
[0042] Take 400g of acenaphthylene, 400mL of xylene, and an appropriate amount of 1,2-bis(p-vinyl)ethane, and put these three substances into a reactor equipped with a stirrer, a condenser, a thermometer, and a 1000mL nitrogen protection device, stir, heat, and slowly raise the temperature of the reaction system to 90°C, and continue stirring for a period of time until the above three substances are completely dissolved, and the solution reaches a uniform state; then, accurately weigh 3.2g of benzoyl peroxide BPO, add it to the reaction system, and stir for 4 hours. During the 4-hour reaction process, the stirrer should continue to stir, the nitrogen protection device should continue to provide nitrogen protection, and the condenser should continue to condense and reflux to ensure the stability of the reaction system. After 4 hours of reaction, the polymerization reaction is completed, and finally a polymerization liquid C is obtained. Through 1H-NMR, GPC and FT-IR analysis, it is confirmed that the polymerization liquid C contains the compound represented by the following structural formula,
[0043]
[0044] The polyacenaphthylene curing agent C has a number average molecular weight of 1,100.
[0045]
[0046] Table 2
[0047] The above multiple embodiments and comparative examples were subjected to performance tests, the test methods are as follows, and the test results are shown in Table 3.
[0048] Physical property test: Referring to IPC TM-650 2.5.5.132007 standard "Relative dielectric constant and loss tangent using split cylinder resonator", take a square-shaped fully cured laminated film sample with a size of 50mm×70mm×0.5mm, and use Keysight Technologies 8722ES to measure the dielectric constant Dk and loss factor Df of the sample at a frequency of 10GHz;
[0049] X / Y-CTE test: After the prepared laminated film was cured at 180°C for 2 hours, a sample was prepared and X / Y-CTE was tested using TA's TMA-450. a1 is the CTE before TG.
[0050]
[0051] Table 3
[0052] The above experimental data are analyzed. It can be seen from Examples 1-6 that the resin composition obtained by curing the polyacenaphthylene curing agent of the present invention with a thermosetting resin can obtain good dielectric properties and a low thermal expansion coefficient, thereby obtaining better processing performance; Compared with Comparative Example 1, Example 2 and Example 6 use different curing agents, and under the same other conditions, the amount of curing agent is very close, and the dielectric constants of the resin compositions obtained by the three are close, and there is no obvious difference, but the dielectric loss of Comparative Example 1 is more than twice that of Example 2 and more than three times that of Example 6, and the thermal expansion coefficients of the comparative examples are nearly twice that of Example 2 and Example 6. It can be seen that the selection of commonly used curing agents, such as cyanate esters, and thermosetting resin curing agents is effective. After curing, a resin composition with excellent dielectric constant can be obtained, but better dielectric loss and thermal expansion coefficient cannot be obtained. By using the polyacenaphthylene of the present invention and a thermosetting resin for curing, a resin composition with excellent dielectric constant, dielectric loss and thermal expansion coefficient can be obtained at the same time; in addition, compared with Examples 1-3, the only difference is that the amounts of polyacenaphthylene curing agents used in the three are different, but there is no obvious difference in performance; and, compared with Example 1 and Example 4, Example 4 uses less inorganic filler, but Example 4 achieves a lower dielectric constant, but the dielectric loss and thermal expansion coefficient are significantly increased. It can be seen that although a lower filler ratio can bring a better dielectric constant, it will have a negative impact on the dielectric loss and thermal expansion coefficient.
[0053] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A polyacenaphthylene curing agent, characterized in that: The structural formula of the polyacenaphthylene curing agent is as follows: R is a hydrocarbon chain segment, and n and m are both integers greater than 1.
2. The polyacenaphthylene curing agent according to claim 1, characterized in that: The n and m are both integers of 1-15.
3. The polyacenaphthylene curing agent according to claim 1, characterized in that: The number average molecular weight of the polyacenaphthylene curing agent is 300-5000.
4. The polyacenaphthylene curing agent according to claim 1, characterized in that: The structural formula of the polyacenaphthylene curing agent is Any one of .
5. A resin composition, characterized in that: It includes the following components in parts by weight: 80-120 parts of thermosetting resin, 0.01-10 parts of curing accelerator, 300-500 parts of inorganic filler and 80-180 parts of the polyacenaphthylene curing agent according to any one of claims 1-4.
6. The resin composition according to claim 5, characterized in that: The thermosetting resin is at least one of polyimide resin, phenoxy resin, polyamide resin, polyamideimide resin, and polyvinyl acetal resin.
7. The resin composition according to claim 5, characterized in that: The number average molecular weight of the thermosetting resin is 2,000-100,000.
8. The resin composition according to claim 5, characterized in that: The curing accelerator is one of an imidazole curing accelerator, a tertiary amine curing accelerator, a phosphine curing accelerator, a photobase generator, and a sulfonium salt curing accelerator; the inorganic filler is at least one of silica, alumina, barium sulfate, talc, clay, mica, magnesium oxide, aluminum hydroxide, aluminum nitride, boron nitride, silicon nitride, glass powder, glass frit, glass fiber, and carbon fiber.
9. The resin composition according to claim 5, characterized in that: The equivalent ratio of the thermosetting resin to the polyacenaphthylene curing agent is 1:(0.3-2).
10. A laminated insulating film, characterized in that: The method is prepared by the following steps: using a coating machine to coat the resin composition described in any one of claims 5 to 9 on a base film, wherein the base film is made of PET or BOPP material; after coating, drying is performed at a temperature of 100°C and a drying time of 10 minutes; after drying, the base film is removed to obtain a laminated insulating film.
Citation Information
Patent Citations
Novel polymer resin for high-frequency and high-speed copper-clad plates
CN113320245A
Novel polymer resin for high-frequency and high-speed copper-clad plate
CN117416106A
Curable resin composition, cured product, dry film, film, prepreg, metal-clad laminate, printed wiring board and electronic apparatus
JP2017125175A